Development of Student Worksheets Integrated with Microlearning Comics for Learning Probability - Komariyatiningsih, Novi; Hartono, Yusuf; Putri, Ratu Ilma Indra; Hiltrimartin, Cecil (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Numerous studies have shown that students face difficulties in learning probability. This study aimed to enhance students’ understanding of the concept of probability while developing their reasoning skills by integrating comics into student worksheets. It focused on designing probability material for grade 10 using the student worksheets and microlearning (comics) that were both effective and efficient. The material was developed using Pendidikan Matematika Realistik Indonesia (PMRI) approach, incorporating a microlearning method within the context of culinary tourism, to enhance students’ understanding of probability and reasoning skills. This study employed a design research methodology in two stages, namely preliminary study and formative evaluation. The subjects of this study were 34 students of grade tenth at Senior High School in Prabumulih. Data collected through observations, tests, and interviews were analyzed descriptively. The study resulted the student worksheets on probability, which were incorporated with microlearning comics whose effectiveness and efficiency were aligned with the characteristics of the PMRI approach. Based on the findings, it can be concluded that the PMRI-based student worksheets that were incorporated with microlearning comics were efficient and effective in helping students develop their reasoning skills. The integration of comics and the PMRI approach reflects a commitment to innovation and the continuous development of effective learning designs that promote inclusive, equitable, and meaningful learning experiences.